Relationship Between Serum Amino Acid Levels and Bone Mineral Density: A Mendelian Randomization Study - Cui, Zhiyong; Feng, Hui; He, Baichuan; He, Jinyao; Tian, Yun (Frontiers in Endocrinology, 2021)
Background This study aimed to explore the association between serum amino acids (AAs) levels and bone mineral density (BMD). Methods We performed a two-sample Mendelian randomization (MR) analysis to analyze the associations between the levels of eight AAs and BMD values by using summary-level genome-wide association study (GWAS) data. We applied the MR Steiger filtering method and MR Pleiotropy RESidual Sum and Outlier (MR-PRESSO) global test to check for and remove single nucleotide polymorphisms (SNPs) that were horizontally pleiotropic. The associations were estimated with the inverse variance weighted (IVW) , MR-Egger, weighted median and MR Robust Adjusted Profile Score (MR.RAPS) methods. Results Our study found that genetically increased Ile (IVW: effect = 0.1601, 95% confidence interval [CI] = 0.0604 ~ 0.2597, p = 0.0016) and Val levels (IVW: effect = 0.0953, 95% CI = 0.0251 ~ 0.1655, p = 0.0078) were positively associated with TB-BMD. The results also revealed that genetically increased Tyr levels were negatively associated with TB-BMD (IVW: effect = -0.1091, 95% CI = -0.1863 ~ -0.0320, p = 0.0055). Conclusions In this study, associations between serum AA levels and BMD were established. These findings underscore the important role that serum AAs play in the development of osteoporosis and provide evidence that osteoporosis can be prevented and treated by the intake of certain AAs.